(untitled) (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. Qualitative functional support of management is an important prerequisite for the success of the organization in the market. Nowadays, the implementation of classical management functions has expanded its content and applied aspect of implementation. This is due to the speed of change in the exogenous and endogenous environments of organizations, their inertia, changing the worldview of the generations that make up the personnel basis of the functional management Goal. The goal of the publications is to analyze the current manifestations of the implementation of management functions, identify current management problems and the formation on this basis of the determination of strengthening the positive effects of functional management. Results. The work highlights the main new features of the implementation of the organization functions, planning, control and motivation. It is substantiated that the characteristic feature of the implementation of the organizational function is the gradual transition to decentralized organizational structures on the basis of adhocracy and holocracy. The priority role of the situational approach for full implementation of the strategy in the development of the organization is defined. New vectors of intra-organizational implementation of the control function have been outlined. It is established that the biggest transformational changes have undergone the function of motivation, which in case of its effective application includes internal organizational manifestations of socially responsible behavior of the organization and a gradual transition to the importance of balancing professional success and personal space. The conducted ABC-analysis allowed to rank the current managerial problems of modern management, to justify the feasibility of scientific research on algorithms for designing organizational structures, to actualize the need to further strengthen the internal value orientations of the organization as a prerequisite for increasing profitability and its share in a particular market.